Analysis of the Interfaces Between GRI and SDGs: a bibliometric review on the WOS platform with a focus on Brazil - Carvalho De Benedicto, Samuel Carvalho de; Gonzalez, Samuel Marchi; Normanha, Bruno de Aguiar; Longo, Regina Márcia (Revista de Administração da UFSM, 2025)
Objective: This study aims to evaluate the relationship between the Global Report Initiative (GRI) and the Sustainable Development Goals (SDGs) of the 2030 Agenda, focusing on publications on the Web of Science (WoS) platform that deal with Brazil. Methodology: The research has a qualitative approach and an exploratory strategy. A bibliometric survey was carried out on the WoS platform, with subsequent descriptive analysis, producing maps and clusters using the VOSViewer software. Results: The WoS database contains a large number of publications dealing with the GRI and SDGs separately and considerably fewer articles dealing with the two topics together. The relationship between the GRI and the SDGs in the port sector is particularly noteworthy. Of the 17 SDGs, only a few are covered in open access publications. Brazil stands out among the countries that have published articles relating the themes together, indicating its importance in research and publication of studies related to sustainable development. Practical implications: We sought to quantify and characterize the publications that address the themes, analysing the nature of the articles published, the predominance of themes, authors, countries and institutions in the spotlight, the proportion of articles that address the two themes together, which SDGs are most addressed in the publications that work on the GRI as a research object, and the relevance of Brazil in the context of research and publications on the themes. Originality: There are few studies that address the two topics dealt with here simultaneously. Therefore, the study seeks to fill a gap found in the scientific literature.